Taxation and the Cost of Capital in Hungary and Poland : A Comparison with Selected European Countries. (IMF Working Papers; Working Paper, 1990)
This paper compares the effective rates of taxation faced by a representative investor located in a major capital-exporting country for investments in machinery and buildings in nine capital-importing European countries. Poland and Hungary are found to have relatively high effective tax rates on equity-financed investment. The analysis suggests that both countries would benefit from streamlining capital cost recovery allowances and possibly lowering statutory corporate tax rates-as permitted by the revenue constraint-rather than providing tax preferences for foreign investors.